The Study of Thermal Decomposition of Natural Calcium Carbonate by the Temperature-programmed Mass Spectrometry Technique - S.N. Danilchenko; V.D. Chіvanov; A.G. Ryabishev; S.V. Novіkov; A.A. Stepanenko; V.N. Kuznetsov; E.V. Mironets; A.V. Marіychuk; A.A. Yanovska; O.G. Bordunova; A.N. Bugay (Журнал нано- та електронної фізики)
The experiments have shown that the heating range for quantitative evolution of carbon dioxide gas (CO2) from natural calcium carbonates (e.g., chalk, corals, shells of the Anadara clams (Anadara inaequivalvis), shell of bird eggs) is from 500 to 850 C with a total heating time of 30-50 minutes. The only exception is the sample of a mortar from a masonry of Saint Sophia Cathedral (the architectural monument of XI century), in which the lowest border of the heating range for carbon dioxide evolution is 400 C. The shape of the CO2 evolution curves for every sample is significantly different in width and intensity as compared to the standard sample (chemically pure synthetic CaCO3). The results, which were obtained on the thermoprogrammed mass-spectrometry (TP‑MS) unit, designed and produced by the authors of the current paper, are of great importance for the development of a gas input technique for radiocarbon dating with accelerator mass-spectrometry.